Isolation of Brucella abortus from a Dog and a Cat Confirms their Biological Role in Re‐emergence and Dissemination of Bovine Brucellosis on Dairy Farms. Issue 5 (15th June 2016) - Wareth, G.; Melzer, F.; El‐Diasty, M.; Schmoock, G.; Elbauomy, E.; Abdel‐Hamid, N.; Sayour, A.; Neubauer, H.
Summary: Brucellosis is highly contagious bacterial zoonoses affecting a wide range of domesticated and wild animals. In this study, Brucella ( B .) abortus bv 1 was identified in uterine discharge of apparently healthy bitch and queen with open pyometra housed on a cattle farm. This study highlights the role of dogs and cats as symptomatic carriers and reservoirs for Brucella . To the best of our knowledge, this study represents the first report of feline infection with B. abortus bv 1 globally. These pet animals may contaminate the environment and infect both livestock and humans. Surveillance and control programmes of brucellosis have to include eradication of the disease in dogs, cats and companion animals.